2011
DOI: 10.5551/jat.10397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Albumin, Serum C-Reactive Protein, and Pulse Wave Velocity as Predictors of the 4-Year Mortality of Chronic Hemodialysis Patients

Abstract: Aim:Although serum albumin and C-reactive protein (CRP) levels and pulse wave velocity (PWV) are known to be associated with the clinical outcome of hemodialysis (HD) patients, it is unknown which of these parameters are more predictive of the long-term mortality of such patients. Methods: We measured biochemical parameters, including serum albumin and CRP, and the PWV of 202 patients on maintenance HD therapy and followed their course for 4 years, and 186 of the patients were enrolled in the current study ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Moreover, clinical and laboratory studies have shown that CRP can reduce serum Alb levels, activate the complement system and stimulate peripheral blood mononuclear cells to synthesize a membrane glycoprotein that activates the clotting response to promote cardiovascular damage [24]. Reduced serum Alb levels may reflect more serious atherosclerosis resulting from the uremic state, other nutrient deficiencies (e.g., folic acid and vitamin B 12 deficiencies cause an increase in homocysteine levels, a risk factor for atherosclerotic heart disease) or the inflammatory state [25] and promote endothelial injury [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical and laboratory studies have shown that CRP can reduce serum Alb levels, activate the complement system and stimulate peripheral blood mononuclear cells to synthesize a membrane glycoprotein that activates the clotting response to promote cardiovascular damage [24]. Reduced serum Alb levels may reflect more serious atherosclerosis resulting from the uremic state, other nutrient deficiencies (e.g., folic acid and vitamin B 12 deficiencies cause an increase in homocysteine levels, a risk factor for atherosclerotic heart disease) or the inflammatory state [25] and promote endothelial injury [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Thirty articles examining the prognostic value of brachial-ankle PWV in prospective studies were identified 63, (Table 3). Of these, four studies examined the prognosis twice in the same cohorts [95][96][97][98] , and only one aggregate data meta-analysis is available to examine the usefulness of brachial-ankle PWV as a predictor of future cardiovascular events 99) . Age is an important determinant of arterial stiffness; therefore, PWV may be considered as a marker of aging, serving as an overall marker of death.…”
Section: Is Brachial-ankle Pwv Useful For Risk Stratification For Carmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] Nonetheless, brachial-ankle PWV measures stiffness of mixed elastic with muscular arteries, 26 instead of the elastic aorta alone, and hence quantitatively differs from carotid-femoral PWV and may have distinct values of cardiovascular prediction. In the present study, we investigated the predictive value of brachial-ankle PWV for mortality in an elderly Chinese population.…”
mentioning
confidence: 99%
“…11 Previous studies have shown that brachial-ankle PWV is closely correlated with carotid-femoral PWV 12 and is also predictive of cardiovascular events and mortality in the general population [13][14][15][16] and in various patient cohorts. [17][18][19][20][21][22][23][24][25] Nonetheless, brachial-ankle PWV measures stiffness of mixed elastic with muscular arteries, 26 instead of the elastic aorta alone, and hence quantitatively differs from carotid-femoral PWV and may have distinct values of cardiovascular prediction. In the present study, we investigated the predictive value of brachial-ankle PWV for mortality in an elderly Chinese population.…”
mentioning
confidence: 99%